Meningkatkan Minat Belajar dan Sifat Kreatif Siswa Melalui Program Merdeka Belajar-Kampus Merdeka - Yulia Sembiring; Fajar Utama (Yayasan Literasi Sains Indonesia, 2023)
This research implements the Merdeka Belajar-Kampus Merdeka (MBKM) Program using the casework method at UPT SD Negeri 064024, specifically in class IV B. Initial observations indicated a low interest in learning among students due to monotonous teaching methods. Through the stages of engagement, assessment, intervention, monitoring, evaluation, and termination, the author successfully increased students' interest in learning and creativity. The learning materials involved animated videos, ice-breaking activities, and handicrafts to develop students' characters. Through an engaging approach, students showed improved curiosity and self-confidence. The implementation of MBKM using the casework method brought about positive changes in the students of class IV B, supporting creative and inquisitive educational goals.